Kajian Yuridis Perlindungan Konsumen Dalam Praktik Fintech (Financial Technology) Ilegal: Studi Putusan Perkara Nomor 3115 K/Pdt/2021 - Billy Sugihono (Lembaga Pengembangan Kinerja Dosen, 2024)
In the era of globalization, financial technology (fintech) has enabled society to access financial services quickly and efficiently. However, the emergence of illegal Fintech presents risks to consumers, such as financial losses and privacy breaches. Legal protection for victims of illegal fintech practices is important to ensure the safety and rights of consumers. This study aims to identify the legal consequences of illegal P2PL Fintech and evaluate legal protection for victims in the context of the case study Decision Number 3115 K/PDT/2021. The study uses a normative juridical method by analyzing relevant legal texts, such as laws, regulations, and court decisions. The results show that the legal consequences of illegal Fintech include law enforcement actions, compensation for victims, regulatory prevention efforts, and improved consumer protection. Victims of illegal Fintech practices receive legal protection from existing regulations and law enforcement. Court decisions, such as Decision Study Number 3115 K/PDT/2021, serve as important legal precedents in addressing these illegal practices. Thus, this research provides a better understanding of consumer protection in illegal fintech practices and emphasizes the importance of strict regulations and effective law enforcement in maintaining the integrity of the fintech industry and public trust.